GAP ANTARA FIKIH MUNAKAHAT DAN UNDANG-UNDANG PERKAWINAN - Khaeruddin Hamsin, Muhammad (Jurnal Media Hukum, 2013)
The existence of marriage law in Indonesia has involved various interests such as religion, state, and women. In this sense, Indonesia expects to have a uniform marriage law in order to reduce gap and tension among the existing legal systems, namely Civil Law (Dutch Law), Adat law and Islamic law (fiqh). The research aims to study critically the reasons behind the gap between Fiqh Munakahah and Marriage Law Act in cause of marriage under age, to find out alternative policy resolving the gap. The research is normative legal research with non-doctrine approach. Both library and field research are conducted. The research find out that the alternative policy to overcome the gap is by enforcing legal sanction in marriage law, promoting more intensive legal awareness in the society and formulating a clearer provision in the marriage law act. Particularly on minimum age for marriage, therefore society might accept the law sociologically and philosophically.